2017
DOI: 10.1177/0883911516688482
|View full text |Cite
|
Sign up to set email alerts
|

Poly(acrylamide co-acrylic acid) for use as an in situ gelling vitreous substitute

Abstract: Our objective is to improve on our previous work developing thiol-containing water-soluble copolyacrylamides that form hydrogels in situ for use as vitreous substitutes. In this study, we evaluate the incorporation of acrylic acid by varying the feed ratio of acrylic acid monomer from 0 to 40 mol% in combination with acrylamide, and bis-acryloylcystamine as the reversible cross-linker. After polymerization, the formed copolymer hydrogels were reduced with dithiothreitol to cleave the disulfide cross-linkers. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The low toxicity of hydrogels-based biomaterials can avoid the extraction of the employed current tamponades (e.g., SiOs, HSiOs) after the chorioretinal adhesion has occurred. Many natural and synthetic polymers showed promising results as hydrophilic tamponades such as HA [ 182 , 183 , 184 , 185 , 186 , 187 , 188 ], alginate [ 183 , 189 ], collagen [ 187 , 190 ], gellan [ 191 , 192 ], chitosan [ 188 , 189 , 193 ], polyvinyl alcohol methacrylate [ 194 ], polyvinyl alcohol [ 195 , 196 , 197 , 198 , 199 ], poly (ethylene glycol) [ 200 ], acrylic acid [ 201 ], acrylamide [ 185 , 202 ], poly N-acryloyl [ 203 ] and glycinamide-polycarboxybetaine acrylamide [ 203 ]. However, the clinical application of many of the previously described materials has been hampered by their lack of transparency, deviating refractive indices, degradation, or poor biocompatibility, and even the toxicity of the crosslinking agents.…”
Section: Classification Of the Vitreous Substitutes: General Principl...mentioning
confidence: 99%
“…The low toxicity of hydrogels-based biomaterials can avoid the extraction of the employed current tamponades (e.g., SiOs, HSiOs) after the chorioretinal adhesion has occurred. Many natural and synthetic polymers showed promising results as hydrophilic tamponades such as HA [ 182 , 183 , 184 , 185 , 186 , 187 , 188 ], alginate [ 183 , 189 ], collagen [ 187 , 190 ], gellan [ 191 , 192 ], chitosan [ 188 , 189 , 193 ], polyvinyl alcohol methacrylate [ 194 ], polyvinyl alcohol [ 195 , 196 , 197 , 198 , 199 ], poly (ethylene glycol) [ 200 ], acrylic acid [ 201 ], acrylamide [ 185 , 202 ], poly N-acryloyl [ 203 ] and glycinamide-polycarboxybetaine acrylamide [ 203 ]. However, the clinical application of many of the previously described materials has been hampered by their lack of transparency, deviating refractive indices, degradation, or poor biocompatibility, and even the toxicity of the crosslinking agents.…”
Section: Classification Of the Vitreous Substitutes: General Principl...mentioning
confidence: 99%
“…Vitreous substitutes must be transparent and permeable. The natural vitreous maintains the shape of the eye by behaving as a viscoelastic fluid or gel [ 12 , 21 ] and a vitreous substitute must mimic this. An ideal vitreous substitute should also not degrade with time [ 15 ].…”
Section: The Ideal Vitreous Substitutementioning
confidence: 99%
“…In vivo rabbit studies of the hydrogel indicated no inflammation or toxicity after 1 week [ 108 ]. Recently, Davis et al [ 21 ] incorporated acrylic acid into the hydrogel formulation. Various concentrations of this hydrogel were developed and characterised.…”
Section: Experimental Polymeric Vitreous Substitutesmentioning
confidence: 99%
“…[18][19][20] There are also subjects studied differently in the literature. 21,22 According to biocompatibility testing in tissue culture with poly(acrylic acid) retinal pigment epithelial cells (ARPE-19), it was found to be a non-toxic polymer of 10 mg/mL compared to controls and polymers with higher concentrations. Unlike the previously reported copolyacrylamide hydrogels, these hydrogels remained optically clean and gelled at low concentrations and have the potential to be used as vitreous substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the previously reported copolyacrylamide hydrogels, these hydrogels remained optically clean and gelled at low concentrations and have the potential to be used as vitreous substitutes. 21 In previous studies, we have investigated the efficacy of different types of antimicrobial polymers against different pathogenic microorganisms. [22][23][24][25][26][27][28][29] This polymer differs from the existing antimicrobial polymers in that it removes harmful properties due to dermatophyte fungi found in the skin, nails and hair.…”
Section: Introductionmentioning
confidence: 99%